Generalized reciprocity and interfirm cooperation: a study of entrepreneurial development in Argentina - Frémeaux, Sandrine (Journal of business ethics, 2026)
Business ethics research on generalized reciprocity, which focuses on the cascade of gifts induced by unconditional giving, often emphasizes the quality of the resulting interpersonal relationships, overlooking the possible development of interfirm cooperation. Our study addresses this gap by answering the following research question: How can generalized reciprocity encourage the emergence and development of interfirm cooperation? Drawing on an analysis of 94 semi-structured interviews with members and partners of a small common good-oriented firm, we revealed the triggers and principles behind generalized reciprocity in the small business context and demonstrated how they facilitate interfirm cooperation. Furthermore, we showed that generalized reciprocity is a possible driving force behind interfirm cooperation through a three-stage process: the collective experience of generalized reciprocity, the collective awareness of the values of generalized reciprocity, and the collective belief in the benefits of generalized reciprocity.